Procalcitonin Improves the Glasgow Prognostic Score for Outcome Prediction in Emergency Patients with Cancer: A Cohort Study. (15th March 2015) - Rast, Anna Christina; Kutz, Alexander; Felder, Susan; Faessler, Lukas; Steiner, Deborah; Laukemann, Svenja; Haubitz, Sebastian; Huber, Andreas; Buergi, Ulrich; Conca, Antoinette; Reutlinger, Barbara; Mueller, Beat; et al.
Abstract : The Glasgow Prognostic Score (GPS) is useful for predicting long-term mortality in cancer patients. Our aim was to validate the GPS in ED patients with different cancer-related urgency and investigate whether biomarkers would improve its accuracy. We followed consecutive medical patients presenting with a cancer-related medical urgency to a tertiary care hospital in Switzerland. Upon admission, we measured procalcitonin (PCT), white blood cell count, urea, 25-hydroxyvitamin D, corrected calcium, C-reactive protein, and albumin and calculated the GPS. Of 341 included patients (median age 68 years, 61% males), 81 (23.8%) died within 30 days after admission. The GPS showed moderate prognostic accuracy (AUC 0.67) for mortality. Among the different biomarkers, PCT provided the highest prognostic accuracy (odds ratio 1.6 (95% confidence interval 1.3 to 1.9), P < 0.001, AUC 0.69) and significantly improved the GPS to a combined AUC of 0.74 (P = 0.007 ). Considering all investigated biomarkers, the AUC increased to 0.76 (P < 0.001 ). The GPS performance was significantly improved by the addition of PCT and other biomarkers for risk stratification in ED cancer patients. The benefit of early risk stratification by the GPS in combination with biomarkers from different pathways should be investigated in further interventional trials.